THE EFFECT OF CASH CONVERSION CYCLE ON PROFITABILITY AND LIQUIDITY: EMPIRICAL STUDY ON PROPERTY AND REAL ESTATE INDUSTRY COMPANIES LISTED IN THE LQ45 INDEX ON THE IDX 2015-2020 PERIOD - Destivani, Audia
The property and real estate industry has a vital role in the Indonesian economy because this industry has a multiplier effect. The property and real estate industry relates to almost all industries that are important to the economy; at least 175 industries are directly or indirectly related to this industry. Seeing the vital role of the property and real estate industry, it is hoped that it will have an excellent performance to move the country’s economy significantly. But in reality, this industry has not shown a good enough performance in Indonesia. The contribution of the property and real estate industry in Indonesia to GDP is the lowest in ASEAN. In 2013-2020, the contribution of the property and real estate sector to GDP was very small, less than 3.1%. In the property and real estate industry, working capital is vital for companies to carry out their business activities. From the standpoint of business characteristics, companies in the property and real estate industry require substantial capital or financing to run and develop their business. Judging from the characteristics of its business, companies engaged in property and real estate require significant capital or financing to run and develop their businesses. The amount of working capital needed by this industry requires companies to be able to manage working capital management (cash conversion cycle) efficiently so that companies can carry out daily business operations and get the maximum profit. This study analyzes the effect of the cash conversion cycle on the company's profitability as measured by return on assets and company liquidity as measured by the current ratio. This study uses SPSS as a statistical analysis tool in performing simple linear regression with a research sample of six property and real estate companies listed on the LQ45 index on the Indonesia Stock Exchange during the 2015-2020 period. This study uses an observation span of six years. The results of this study indicate that the cash conversion cycle has a negative and significant effect on company profitability (Return On Asset). In addition, this study shows that the cash conversion cycle has a positive and significant impact on company liquidity (Current Ratio).